Prognostic value of (18) F-fluoroazomycin arabinoside PET/CT in patients with advanced non-small-cell lung cancer - Saga, Tsuneo; Inubushi, Masayuki; Koizumi, Mitsuru; Yoshikawa, Kyosan; Zhang, Ming-Rong; Tanimoto, Katsuyuki; Horiike, Atsushi; Yanagitani, Noriko; Ohyanagi, Fumiyoshi; Nishio, Makoto (Cancer science, 2015)
This study evaluated the prognostic value of positron emission tomography/computed tomography (PET/CT) using (18) F-fluoroazomycin arabinoside (FAZA) in patients with advanced non-small-cell lung cancer (NSCLC) compared with (18) F-fluorodeoxyglucose (FDG). Thirty-eight patients with advanced NSCLC (stage III, 23 patients; stage IV, 15 patients) underwent FAZA and FDG PET/CT before treatment. The PET parameters (tumor-to-muscle ratio [T/M] at 1 and 2 h for FAZA, maximum standardized uptake value for FDG) in the primary lesion and lymph node (LN) metastasis and clinical parameters were compared concerning their effects on progression-free survival (PFS) and overall survival (OS). In our univariate analysis of all patients, clinical stage and FAZA T/M in LNs at 1 and 2 h were predictive of PFS (P = 0.021, 0.028, and 0.002, respectively). Multivariate analysis also indicated that clinical stage and FAZA T/M in LNs at 1 and 2 h were independent predictors of PFS. Subgroup analysis of chemoradiotherapy-treated stage III patients revealed that only FAZA T/M in LNs at 2 h was predictive of PFS (P = 0.025). The FDG PET/CT parameters were not predictive of PFS. No parameter was a significant predictor of OS. In patients with advanced NSCLC, FAZA uptake in LNs, but not in primary lesions, was predictive of treatment outcome. These results suggest the importance of characterization of LN metastases in advanced NSCLC patients.